The protective effect of Limosilactobacillus reuteri against gestational diabetes mellitus through restoring intestinal microbiota homeostasis and attenuating inflammation in mice - Ce Qi; Haowen Zhang; Zhenli Liu; Xiaolin Liu; Lintao Zhang; Liangliang You; Jin Sun (Food Science and Human Wellness)
Limosilactobacillus reuteri QS01 is potential probiotic isolated from the intestinal microbiota of healthy women in early pregnancy. In the current study, we examined whether QS01 can prevent gestational diabetes mellitus (GDM) in an enhanced mouse model of the condition. Female C57BL/6J mouse offspring (F1 generation) born to dams fed a control (CON) or low-protein diet (GDM group) during gestation and lactation were used. Pregnant F1 mice fed a standard diet were randomly assigned to 5 groups: CON, GDM, and GDM mice treated with metformin, QS01 or Lacticaseibacillus rhamnosus HN001. An oral glucose tolerance test was performed before sacrifice at gestational day 17. Glucose tolerance was significantly ameliorated by all 3 treatments. QS01 supplementation fortified the intestinal mucosal barrier and inhibited the escalation of plasma inflammatory cytokines. QS01 treatment altered the cecal microbiota composition and function. Plasma and cecal metabolite profiles were modulated by QS01, prominently demonstrating significant upregulation of indole lactate and L-tryptophan in plasma and 5-hydroxy-tryptophan in the cecum, positively correlated with gut Lactobacillus abundance. In summary, QS01 plays a role in preventing GDM by remodeling the intestinal microbiota, reinforcing the intestinal mucosal barrier and alleviating chronic inflammation.